Energy audit in Faculty of Mechanical Engineering UiTM Shah Alam, Selangor: article - Sharif, Ahmad Fauzi (Faculty of Electrical Engineering, 2010)
People nowadays are more concerned about energy efficiency and conservation. One of the focal points of such concern is on energy consumption in buildings. An energy audit is considered as one of the comprehensive methods in checking energy usage and wastage in buildings. This paper addresses the implementation method of energy saving in Faculty of Mechanical Engineering (FKM) at Universiti Teknologi MARA (UiTM) Shah Alam, Malaysia. In this paper, energy saving concept and purpose is analyzed. By analyzing current utilization situation of energy in FKM building, the significance of energy saving in FKM building to produce improvement in operation efficiency and cost saving initiatives due to high monthly electrical consumption and penalty charge due to low power factor operation by the supply utility. Power quality, harmonic and power factor issues are successfully identified and recommendation for improvement is highlighted.